2016
DOI: 10.1590/abd1806-4841.20163817
|View full text |Cite
|
Sign up to set email alerts
|

Paronychia and granulation tissue formation during treatment with isotretinoin

Abstract: This paper describes the association of two unusual side effects of treatment with isotretinoin for severe acne: paronychia and excess granulation tissue in the nails furrows. We report a case of male patient aged 19 years, who in the course of the 36th week of treatment with isotretinoin for acne grade III showed erythema, edema, excess granulation tissue and onychocryptosis in various nail beds of hands and feet, with no history of trauma associated. A literature review revealed few reports of these adverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 10 publications
2
9
0
Order By: Relevance
“…Herein we report the case of a single patient who experienced both onychocryptosis and external urethritis while on isotretinoin therapy for acne vulgaris. Similar to previously documented cases,6–8 his asymptomatic external urethritis spontaneously resolved on completion of his isotretinoin regimen, but his onychocryptosis required surgical intervention. His story helps shed light on a potential treatment paradigm for these uncommon adverse events.…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…Herein we report the case of a single patient who experienced both onychocryptosis and external urethritis while on isotretinoin therapy for acne vulgaris. Similar to previously documented cases,6–8 his asymptomatic external urethritis spontaneously resolved on completion of his isotretinoin regimen, but his onychocryptosis required surgical intervention. His story helps shed light on a potential treatment paradigm for these uncommon adverse events.…”
Section: Introductionsupporting
confidence: 79%
“…While his paronychia and granulation tissue resolved after completing his isotretinoin regimen, onychocryptosis in his hallux persisted and required matrixectomy for complete resolution. Excessive development of granulation tissue was suggested to be a mechanism for his symptoms 6. One theory suggests that excess retinoids may disrupt the nail matrix at the epithelial level generating local dermatitis with accumulation of scales in the nail folds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 It has also been reported after treatment with topical and/or systemic retinoids-such as isotretinoin-between two weeks and six months after the initiation of treatment. 3,4 Most cases reported in the literature are located in the periungual area (i.e. lateral and distal nail folds), although it can also affect the chest, back, face, scalp and, less frequently, the genital area, as in the present case.…”
Section: Commentsupporting
confidence: 49%
“…[6] It has been reported that the resolution of excess granulation tissue secondary to systemic retinoid therapy occurs on withdrawal of isotretinoin. [7] Unfortunately for our patient, discontinuation of isotretinoin and prevention of secondary infection in areas of excess granulation tissue was insufficient in resolving these lesions. To date, there is no consensus evidence based approach to the treatment of isotretinoin induced pyogenic granulomas.…”
Section: Introductionmentioning
confidence: 75%